Microglia-orchestrated neuroinflammation and synaptic remodeling: roles of pro-inflammatory cytokines and receptors in neurodegeneration - Yang, Guang; Xu, Xiao; Gao, Waimao; Wang, Xingyu; Zhao, Yan; Xu, Ying (Frontiers in Cellular Neuroscience, 2025)
Microglia, the innate immune cells of the central nervous system (CNS), play essential roles in maintaining neural homeostasis through dynamic interactions with neurons and other brain structures. While their protective functions are well-established, recent studies have illuminated the detrimental consequences of sustained microglial activation in the context of neurodegeneration. In particular, overactivated microglia contribute to neuroinflammation and induce synaptic alterations through the release of pro-inflammatory cytokines and engagement of specific receptors. These interactions disrupt synaptic structure and function, compromising connectivity, plasticity, and cognitive processes. Notably, neuronal synapses are primary targets of such inflammation-driven dysfunction, where prolonged exposure to cytokines such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α), and signaling via receptor systems including cluster of differentiation-200 (CD200)/CD200 receptor (CD200R), C-X3-C motif chemokine ligand 1 (CX3CL1)/CX3C receptor 1 (CX3CR1), colony-stimulating factor 1 (CSF1)/CSF1 receptor (CSF1R), and interferon-γ (IFN-γ)/IFN-γ receptor (IFN-γR), lead to impaired learning, excitotoxicity, and neurodegenerative progression. This review synthesizes emerging evidence on the mechanisms by which microglia-mediated immune responses regulate synaptic remodeling, emphasizing the roles of pro-inflammatory cytokines and their receptors in neurodegenerative disorders.